Answers

2014-11-12T18:25:42+05:30
3 tan67⁰÷cot23⁰₊1÷2 sin42⁰÷cos48⁰₊5÷2 cosec61⁰÷sec29⁰

= 3 tan 67 / tan (90-23) + 1 / 2 sin 42 / sin (90-48) + 5 / 2 cosec 61 / cosec (90-23)

(SINCE cot theta = tan (90 - theta) ; cos A = sin (90 -A) ; sec B = cosec (90-B)

=[ 3 (tan 67 / tan 67) ]+ [1 / 2 (sin 42 / sin 42) ] + [  5 /  2 (cosec 61 / cosec 61)}

= 3 + 1/2 + 5/2

=3 + 3

=9
0
2014-11-13T16:55:08+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
You should use parentheses when writing algebraic expressions.  It is not clear sometimes, which factor is in numerator and which is in denominator.  The answer can be one of the following.

3\frac{ Tan\ 67}{Cot\ 23}+\frac{1}{\frac{2\ Sin\ 42}{Cos\ 48}}+\frac{5}{\frac{2\ Cosec\ 61}{Sec\ 29}}\\\\=3\frac{tan\ 67}{Cot(90-67)}+\frac{1}{2}\frac{Cos48}{Sin42}+\frac{5}{2}\frac{Sec29}{Cosec61}\\\\=3\frac{tan67}{tan67}+\frac{1}{2}\frac{Cos58}{Sin(90-58)}+\frac{5}{2}\frac{sin61}{cos29}=3+\frac{cos58}{cos58}+\frac{5}{2}\frac{sin61}{Cos(90-61)}\\\\=3+1/2+5/2=6\\\\

==================================

3\frac{ Tan\ 67}{Cot\ 23}+\frac{1}{2\ Sin\ 42\ *\ Cos\ 48}+\frac{5}{2\ Cosec\ 61\ *\ Sec\ 29}\\\\=3\frac{ Tan\ 67}{Cot\ (90-67)}+\frac{1}{2\ Sin\ 42\ *\ Cos(90-42)}+\frac{5}{2}Sin\ 61\ *\ Cos\ 29\\\\=3\frac{Tan\ 67}{Tan\ 67}+\frac{1}{2\ Sin^2\ 42}+\frac{5}{2}Sin\ 61*Sin61\\\\=3+3.029=6.029\\

0
click on the thank you link below the answer